A influência da governança corporativa na sustentabilidade econômica de instituições de ensino superior privadas - Martins, Sara Pedrini (Universidade do Vale do Rio dos Sinos, 2024)
Corporate governance has been the subject of studies around the world for years, especially in the business context. In implementing it, is clear that organizations are looking for tools to help them improve their management model, ensuring transparency in their information and balance in guaranteeing the interests of all stakeholders, which are conditions for ensuring their sustainability. In this sense, private for-profit higher education institutions, like other business organizations, can benefit from corporate governance, especially given the changes in the Brazilian educational scenario, which is increasingly competitive, with a reduction in the number of enrolments and growing mergers and acquisitions by publicly traded educational groups. The purpose of this study was to analyze how corporate governance practices influence the economic sustainability of a private higher education institution. To this end, a qualitative, descriptive study was carried out, based on a single case study of Atitus Educação. Data was collected through document analysis and semi-structured interviews with participants who knew and experienced corporate governance at the institution. The results show that the institution adopts a system of corporate governance and that some of the governance practices, albeit indirectly, influence its economic sustainability, such as the implementation of the executive board and the board of directors, especially when the composition includes independent directors; the existence of internal auditing and independent auditing; the definition and monitoring of academic quality guidelines; and the adoption of strategic management tools, accompanied by continuous monitoring of performance indicators.
Keywords: Governança corporativa; Instituições de ensino superior privadas; Sustentabilidade econômica; Corporate governance; Private higher education institutions; Economic sustainability; ACCNPQ::Ciências Humanas::Educação